2011
DOI: 10.1098/rsif.2011.0114
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant properties of a biocompatible thermo-responsive polymer of N -isopropylacrylamide in autoimmunity and arthritis

Abstract: To evaluate the thermo-responsive poly(N-isopropylacrylamide) (PNiPAAm) polymer as an adjuvant, we synthesized PNiPAAm through free radical polymerization and characterized it both in vitro and in vivo. The polymer when mixed with collagen type II (CII) induced antigen-specific autoimmunity and arthritis. Mice immunized with PNiPAAm-CII developed significant levels of CII-specific IgG response comprising major IgG subclasses. Antigen-specific cellular recall response was also enhanced in these mice, while negl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Recently we evaluated the adjuvant property of PNiPAAm having Mw 120 kDa in mice using two different antigens. 25 When the CII was mixed with PNiPAAm, most of the CII protein retained its native configuration. We tested the adjuvant efficiency of PNiPAAm with molecular weights of 70 and 120 kDa, and found that physical adsorption and high molecular weight (120 kDa) form of moderately hydrophobic PNiPAAm seems to be more optimal to induce a significant adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently we evaluated the adjuvant property of PNiPAAm having Mw 120 kDa in mice using two different antigens. 25 When the CII was mixed with PNiPAAm, most of the CII protein retained its native configuration. We tested the adjuvant efficiency of PNiPAAm with molecular weights of 70 and 120 kDa, and found that physical adsorption and high molecular weight (120 kDa) form of moderately hydrophobic PNiPAAm seems to be more optimal to induce a significant adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the adjuvant efficiency of PNiPAAm with molecular weights of 70 and 120 kDa, and found that physical adsorption and high molecular weight (120 kDa) form of moderately hydrophobic PNiPAAm seems to be more optimal to induce a significant adaptive immune response. 25 Although PNiPAAm does not have any known pathogen-associated molecular pattern (PAMP) ligands, it still induces a broad range of cytokine response (IL-1␤, IFN-␥, IL-4, and IL-17). Thus, PNiPAAm offers opportunities to study the actual autoimmune responses to self-protein(s).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations